Effects of aqueous smoke solutions and heat on seed germination of herbaceous species of the Sudanian savanna-woodland in Burkina Faso - Dayamba, Sidzabda Djibril; Sawadogo, L.; Tigabu, M.; Savadogo, P.; Zida, D.; Tiveau, D.; Oden, P.C. (2010)
Smoke generated by burning of plant materials has widely been recognized as a germination cue for some species from both fire prone and fire-free ecosystems. It is an important factor for the understanding of vegetation dynamics and could have potential use for ecological management and rehabilitation of disturbed areas. Individual species, however, seem to have a specific requirement for the type and dosage of smoke treatments. In the present study, six different concentrations of smoke solution were tested on 13 herbaceous species by soaking the seeds for 24 h. The germination of a forb species, Borreria scabra, was significantly stimulated (p < 0.05) by the smoke treatment while that of the annual grass species, Euclasta condylotricha, was significantly inhibited (p < 0.05) by 100% smoke solution treatment. Contrary to our expectation that another fire-related cue, heat shock, would break the physical dormancy of the species tested, it was not promotive. For non-dormant seeds of B. scabra and Borreria radiata, high temperatures were lethal while low temperature induced physiological dormancy that was overcome in the former species within 30 days of the germination trial. For some species, responses to smoke did not corroborate with the field-observed response to fire, making ecological interpretation challenging. For responsive species, the smoke treatment could be a simple approach for promoting their re-establishment in areas where it is needed. More investigations are needed to assess the spread of response to smoke.